Pediatric Hypertension: Update - Tammy M. Brady (Frontiers Research Topics, 2018)
Hypertension and its resultant complications do occur in childhood and track into adulthood. It's estimated that > 3% of all children have hypertension, with an even greater prevalence among obese children (20-47%). The etiology of hypertension is generally described as primary (essential) or secondary with most secondary causes related to cardio-renal disease. While primary hypertension is on the rise, all children should undergo an evaluation to investigate for a secondary cause of their hypertension. Mild to moderate hypertension is most commonly asymptomatic but may be associated with subtle cardiac, renal, neurological and/or psychosocial.